Does the relation between information quality and capital structure vary with cross-country institutional differences? - CHEN, Jeff Zeyun (Institutional Knowledge at Singapore Management University, 2016)
Prior research based on U.S. data finds that firms with better information quality raise more equity whereas firms with poorer information quality prefer to issue debt when they seek external financing. Little is known about whether the same conclusion holds outside the U.S. and how the country-level institutional environment influences the relation between information quality and capital structure choices. We examine the relation between accounting information quality (measured by earnings precision, accruals quality, and analyst consensus) and financial leverage across 24 countries and whether that relation varies systematically with country-level investor protection and financial orientation. We document a lower financial leverage for firms with better information quality. More importantly, we find a stronger relation between information quality and financial leverage in countries with weaker investor protection and more market-oriented economies. These cross-country results suggest that information quality is especially important in shaping a firm's capital structure decision when investor demand for information is greater.